Pengaruh Model Pembelajaran Think Talk Write (TTW) berbantuan LKPD dengan Teori Polya terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas V SD Negeri 2 Batubulan Gianyar - Cahyani, Ni Putu Dila; Redana, Made; Witraguna, Kadek Yudista (Circle: Jurnal Pendidikan Matematika, 2024)
This study aims to evaluate the impact of the Think Talk Write (TTW) learning model supported by LKPD based on Polya's theory on fifth-grade students' problem-solving skills in mathematics at SD Negeri 2 Batubulan. The study employs a quasi-experimental design with a pre-post non-equivalent control group design, involving two groups of fifth-grade students: the experimental group and the control group. Participants were selected using random sampling, and data were collected through tests designed to measure problem-solving abilities in mathematics. Data analysis was conducted using descriptive statistics to examine score distributions and inferential statistics to test hypotheses. The results indicate that the experimental group achieved an average n-gain of 0.71 (high category), while the control group had an average n-gain of 0.57 (medium category). The t-test showed a t-value of 10.461 compared to a t-table value of 1.991 for df = 76, with a significance value of 0.000 (< 0.05). These findings suggest that the TTW model, supported by LKPD based on Polya's theory, has a significant impact on improving students' problem-solving skills in mathematics.